An - Britten, Benjamin (Oxford University Press, 1963)
Learning to read music, and learning its grammar, need not be dull or too much trouble, writes Benjamin Britten in his Foreword to this book. An introduction to the language of music, designed for the amateur musician, An ABC of Music surveys all the musical terms and ideas likely to be met in the beginning stages of learning to play an instrument. A short, practical guide to the essentials of rudiments, harmony, and form, it is capable of being read straight through with pleasure and understanding, but may also be used as a sort of cumulative dictionary, with each definition leading on to the next